Measurement and detection of radiation. Nicholas Tsoulfanidis, Sheldon Landsberger. - Tsoulfanidis, Nicholas, 1938-; Landsberger, Sheldon (Boca Raton, FL : CRC Press, 2011)
'The research and applications of nuclear instrumentation have grown substantially since publication of the previous editions. With the miniaturization of equipment, increased speed of electronic components, and more sophisticated software, radiation detection systems are now more productively used in many disciplines, including nuclear nonproliferation, homeland security, and nuclear medicine. Continuing in the tradition of its bestselling predecessors, measurement and detection of radiation, third edition illustrates the fundamentals of nuclear interactions and radiation detection with a multitude of examples and problems. It offers a clearly written, accessible introduction to nuclear instrumentation concepts. New to the third edition. A new chapter on the latest applications of radiation detection, covering nuclear medicine, dosimetry, health physics, nonproliferation, and homeland security. Updates to all chapters and subtopics within chapters, as needed. Many new references and a completely updated bibliography. This third edition of a classic textbook continues to serve new students entering the nuclear science and engineering fields. It enables them to select the proper detector, analyze the results of counting experiments, and perform radiation measurements that follow proper health physics procedures. A solutions manual is available with qualifying course adoption'--Provided by publisher.
'The field of nuclear instrumentation has greatly increased both in basic research and applications, since the appearance of the 2nd edition of this book. With the miniaturization of equipment and increased speed of electronic components, radiation detection systems are now more productively used in many disciplines. In particular, areas of nuclear non-proliferation, homeland security, and nuclear medicine all have benefitted from these technological advances. With the emergence of the internet in the 1990's the dissemination of information is also much readily available. While the number of nuclear engineering programs has remained more or less constant in the United States, over the last 20 years, there are now many new academic programs that have nuclear and science and engineering as part of their undergraduate curriculum'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Radiation -- Measurement; Nuclear counters